Polish adaptation of the Dimensional Anhedonia Rating Scale (DARS) - validation in the clinical sample - Gorostowicz, Aleksandra; Rizvi, Sakina J.; Kennedy, Sidney H.; Chrobak, Adrian Andrzej; Dudek, Dominika; Cyranka, Katarzyna; Piekarska, Joanna; Krawczyk, Eve; Siwek, Marcin (Frontiers in Psychiatry, 2023)
Background: Anhedonia is the core symptom of depression. Its presence has been linked to worsened prognosis. The Dimensional Anhedonia Rating Scale (DARS) is a scale measuring desire, motivation, effort and consummatory pleasure across different domains. The aim of this paper was to confirm factor structure, assess reliability and validity of the Polish adaptation of the DARS in a clinical sample of patients with mood disorders and healthy controls (HC). Methods: The study sample included 161 participants aged 18-65 years - 34 HC, 72 patients with bipolar disorder and 55 with major depressive disorder (in depressive episode or remission). Reliability of the Polish adaptation of the DARS was assessed using Cronbach’s α and the average inter-item correlation (AIC). Convergent and divergent validity was established by Pearson’s correlations between the DARS and the Snaith-Hamilton Pleasure Scale (SHAPS), the Quick Inventory of Depressive Symptomatology- self-report (QIDS-SR), the Hospital Anxiety and Depression Scale (HADS). The structure of the scale was examined by factor analysis. Results: The factor structure was consistent with the original scale. Strong internal consistency for the DARS total score (Cronbach’s α=0.95) and all subscales (0.86-0.93) was observed. The DARS demonstrated good convergent (moderate to strong correlations with measures of anhedonia and depression) and divergent validity (weak correlations with anxiety level). Conclusions: The Polish DARS demonstrated excellent internal consistency and very good validity. The scale is a valuable contribution to the psychometrics of anhedonia measures in patients with mood disorders.